Wuzi Yanzong Pill relieves CPZ-induced demyelination by improving the microenvironment in the brain. Issue 12 (December 2022) - Li, Yan-Rong; Sun, Meng-Ying; Hang, Wei; Xiao, Qi; Fan, Hui-Jie; Jia, Lu; Jin, Xiao-Ming; Zhang, Bo; Xiao, Bao-Guo; Ma, Cun-Gen; Chai, Zhi
Abstract: Ethnopharmacology relevance: Wuzi Yanzong Pill (WYP), a well-known prescription for invigorating the kidney and essence, which is widely used to treat infertility such as oligoasthenospermia. Studies have shown that WYP can be used to treat neurological diseases, but its therapeutic effects and mechanisms for multiple sclerosis (MS) remain unclear. Aim of the study: Based on the establishment of Cuprizone (CPZ)-induced demyelination model, this study determined the effect of WYP on remyelination by detecting changes in the microenvironment of the central nervous system. Materials and methods: C57BL/6 mice were divided into three groups. The CPZ group and CPZ + WYP group were fed with 0.2% CPZ feed, and the control group was fed normal feed, for 6 weeks. At the end of the second week, the CPZ + WYP group was gavaged with WYP solution (16 g/kg/d), and the other two groups were gavaged with normal saline twice a day with an interval of 12 h each time, for 4 weeks. Forced swimming and elevated plus maze were used to detect changes in anxiety and depression before and after treatment. Luxol fast blue staining and the expression of MBP were used to evaluate the demyelination of the brain. Western blot was used to detect the expression of microglia and their subtype markers Iba-1, Arg-1, iNOS, the expression of neurotrophic factors BDNF, GDNF, CNTF, and the expression of oligodendrocyte precursor cells NG2. ELISA detected the content of IL-6, IL-1β, IL-10, TGF-β, BDNF, GDNF, CNTF in the brain. The distribution of Iba-1 in the corpus callosum was observed by immunofluorescence. Results: The results showed that on the basis of improving mood abnormalities and demyelination, WYP reduced the protein content of Iba-1 and iNOS, increased the protein content of Arg-1, and reduce accumulation of microglia in the corpus callosum. In addition, WYP reduced the secretion of IL-6 and IL-1β while promoting the secretion of IL-10 and TGF-β. After WYP intervention treatment, the levels of neurotrophic factors BDNF, GDNF, CNTF increased. Due to the improvement of inflammatory and nutritional environment in the CNS, promoting the proliferation of NG2 oligodendrocyte, increased the expression of MBP, and repairing myelin sheath. Conclusion: Our results indicated that WYP promoted the proliferation and development of oligodendrocytes by improving the CNS microenvironment, effectively alleviating demyelination. Abstract : Wuzi Yanzong Pill; Neuroinflammation; Nutritional factors; Oligodendrocyte; Remyelination.